Spatial and temporal behavior of soluble manganese at the sediment-water interface in the Riogrande II reservoir in Colombia. (2015)
ABSTRACT: The behavior of manganese (Mn) at the sediment–water interface in bodies of water such as lakes and reservoirs is dependent on physicochemical factors such as pH, redox potential-Eh, organic matter, specific conductance, and the presence of organic and inorganic complexes. These allow the mobilization of Mn from the sediment to the water column and promote its precipitation as Mn oxyhydroxide. For the Riogrande II reservoir in Colombia (2550 m), it was found that redox potential-Eh below +350 mV is not appropriate for oxide stability. The availability and mobility of these oxides are more associated with organic complexation and desorption from sediments when the pH changes from neutral conditions to slightly acidic conditions (6.0). However, when the lower gates of the reservoir are opened during the dry season, the entry of oxygenated bottom currents most likely increases the dissolved oxygen (DO) and redox potential-Eh. Similarly, the increase in soluble Mn at the intake tower during the dry season is more associated with desorption than with reductive dissolution. The primary objective of this study is to determine the main physicochemical factors favoring Mn remobilization from sediment to the water column and its relation to the operating mechanisms of the intake water tower of the Riogrande II reservoir. One of the most notable results of this study is the observation that the operating mechanisms of the Riogrande II reservoir not only affect the type of water that is captured but also influence the geochemical processes at the bottom of the reservoir and in the sediment. The results of this study highlight the influence of hydraulic processes on surface water bodies as regards the dynamics of metal remobilization, the generation of pollution into the water column, and the increasing costs of treatment and purification in reservoirs in high mountain areas in tropical countries.